A review of recent Cryptosporidium hominis and Cryptosporidium parvum gp60 subtypes - Deborah B. Oladele; Martin Swain; Guy Robinson; Amanda Clare; Rachel M. Chalmers (Current Research in Parasitology and Vector-Borne Diseases, 2025)
Cryptosporidium spp. are known to cause gastroenteritis (cryptosporidiosis) in numerous hosts, including humans. Understanding the diversity within this genus of parasites requires accurate subtyping, which is frequently performed by sequencing part of the gp60 (60-kDa glycoprotein) gene. This literature review examines Cryptosporidium hominis and Cryptosporidium parvum gp60 subtypes reported between December 2018 and January 2024 in humans, livestock, and non-human primates (NHPs). The review highlights emerging trends in the subtypes reported and reveals the shifting dominance of subtype families, which can be influenced by factors such as anthroponotic interactions. The C. parvum IIa and IId families remain major contributors to infections across a variety of hosts, with recent reports indicating the continued emergence of the IId family. Furthermore, previously established and newly reported subtypes detected in NHPs highlight the potential for genetic recombination between human-adapted and NHP-adapted subtypes.